PENGARUH KUALITAS PRODUK, HARGA DAN STORE ATMOSPHERETERHADAP MINAT BELI KONSUMEN PADA TOKO EMAS DAN MUTIARA DISEKARBELA KOTA MATARAM - Yusi Faizathul Octavia (Master of Management, Mataram University, 2015)
This study aimed to analyze the significant influence between product quality, price,and store atmosphere toward consumer purchase intention on the gold and pearl store inSekarbela Mataram city. Intake of respondents conducted with convenience samplingtechnique using a questionnaire distributed to 100 respondents. The data analysis techniqueused is multiple linear regression analysis. Based on the analysis conducted, it can beconcluded that the variable quality of the product, price, and store atmosphere positive andsignificant impact toward consumer purchase intention on the gold and pearl store inSekarbela Mataram city. This means that if the quality of the product, price, and storeatmosphere is enhanced by the gold and pearls shop owners in Sekarbela city of Mataram,can be increasing the consumer purchase intention. While the dominant variable affectingconsumer purchase intention is the store atmosphere variable.Keywords:Quality of Product, Price, Store Atmosphere and Purchase Intention.